4j-8-3j=6

Simple and best practice solution for 4j-8-3j=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4j-8-3j=6 equation:


Simplifying
4j + -8 + -3j = 6

Reorder the terms:
-8 + 4j + -3j = 6

Combine like terms: 4j + -3j = 1j
-8 + 1j = 6

Solving
-8 + 1j = 6

Solving for variable 'j'.

Move all terms containing j to the left, all other terms to the right.

Add '8' to each side of the equation.
-8 + 8 + 1j = 6 + 8

Combine like terms: -8 + 8 = 0
0 + 1j = 6 + 8
1j = 6 + 8

Combine like terms: 6 + 8 = 14
1j = 14

Divide each side by '1'.
j = 14

Simplifying
j = 14

See similar equations:

| y-3=4/7(x-1) | | 86.4=(5.62)5X | | (3x-8)+(10x-73)= | | 86+79+x=85 | | 16-14y+13+18y= | | 9(x^2)-8(x)-48=0 | | 2x+28=0.4 | | 2(4-2r)=-r+5 | | -8+x+14=5 | | 5.45x-2.3=7.2x-3.71 | | 6(1-4w)=-16 | | 2=x^3+1.5 | | 2x+7+5x-4+3x+5=68 | | 3/9*2/7 | | x/8=12-16 | | 5x-(3x+1)=4x-9 | | 4x^2-5x-2x=0 | | 4x+3y=-33 | | (3a+5)-4=-22 | | 5.45-2.3=7.2x-3.71 | | 8(4p+q)=32p+8 | | 28.81/4.3 | | 4+8-4m=8 | | 5(2x-3x)-6x=9 | | 3c+10=2c | | 25(3x+1)+36x+12=1258 | | 5/m=8/2m-6 | | X+31=4y | | 9x-8x=x^2 | | 3y-8+4y=17 | | 9*1/1000= | | 1+3.5*1+10=55 |

Equations solver categories